AN ANALYSIS OF THE MAIN CHARACTER’S PERSONALITY DEPICTED IN THE NOVEL A THOUSAND SPLENDID SUNS BY KHALED HOSSEINI - Ismiana, Fatwatul (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2024)
One of the most phenomenal personality theories is the one proposed by the famous psychologist Sigmund Freud, which has become a reference for millions of analyses for various literary works such as films, novels, and other literary works. Therefore, the reference to Sigmund Freud is inevitable and mandatory considering the importance and significance of Freud's contribution to this universe. Especially Freud's ideas on personality theory relating to the id, ego, and superego. In this analysis, Khaled Hosseini's novel A Thousand Splendid Suns with the main character named Maryam will be the main object in discussing the application of Freud's personality theory. The analysis in this study has the main purpose of finding the results of a character's personality in the story or novel described and the various factors that affect the character's personality changes in the story.